Strategic Openness of Digital Platforms - März, Gabriel (My University, 2021)
This thesis provides a conceptualization of the different dimensions of platform openness, as well as of their strategic parameters and influences, for consolidating and advancing research on digital platforms. In contrast to most research, it is aimed to provide a unifying theory for all platform types and to bridge the technologically oriented and economic streams of research on digital platforms. Next to providing a more comprehensive definition of platform openness, this thesis provides an overview over the strategic dimensions of openness, their interrelations, and their associated tradeoffs. These dimensions have been developed by the means of a structured literature review and have been conceptualized in a taxonomy. Furthermore, several frameworks have been developed, that supplement the insights and structure of this paper, that visualize the interdependencies and tradeoffs of the different dimensions, and that support optimal decision making. Overall, three important meta-dimensions regarding platform openness could be identified, which are the distribution of power including the associated strategic boundary setting, technical decision making, and managerial decision making. The inclusive treatment of these meta-dimensions helped in evincing interdependencies and facilitated the drawing of conclusions regarding the effects of different parameters in this complex topic. It was shown that the tension of autonomy vs. control is especially relevant for platforms with complementing participants. For all kinds of platforms, the consideration and understanding of the participants’ respective costs and needs is important to determine major factors influencing their participatory behavior. Thereby, the influence of “soft” parameters, like trust, engagement, etc. must not be forgotten. The desirability of participation depends on the strategic objectives of the platform provider and on market characteristics and can be influenced by impacting the participant’s costs and benefits. Overall, the correct management of the openness parameters facilitates strategic attainment.
Keywords: Digital Platforms, Platform Openness, Platform Pricing, Management of Boundary Resources, Digital Ecosystems, Platform Economics, Open Innovation, Two-Sided Markets, Platform Governance, Decision Rights, Platform Strategy